Film, method for producing same, laminated structure, laminated glass, and automobile

By using a thermoplastic resin film with specific heat shrinkage properties, the problem of uneven deformation of the film during the heating and pressing process of laminated glass was solved, thus achieving laminated glass with high appearance and design flexibility.

CN119604564APending Publication Date: 2025-03-11TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380055223.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-21
Filing Date
2023-09-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the prior art, the film of laminated glass is prone to uneven deformation during the heating and pressing process, resulting in poor appearance, and the film is not adaptable enough to the heating process.

Method used

A thermoplastic resin film with specific heat shrinkage characteristics is used. By controlling the heat shrinkage rate and the difference in heat shrinkage stress, it is ensured that the film does not produce uneven deformation during the heating and pressing process, thereby improving the adhesion with the intermediate layer and the support.

Benefits of technology

It effectively suppresses appearance defects in laminated glass, improves processing adaptability, and ensures the appearance and design of laminated glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005251324000000261
    Figure BDA0005251324000000261
  • Figure BDA0005251324000000271
    Figure BDA0005251324000000271
  • Figure BDA0005251324000000281
    Figure BDA0005251324000000281
Patent Text Reader

Abstract

The present invention addresses the problem of providing a film which is highly adaptable to a step for laminating a functional layer in association with heating, and which is capable of suppressing uneven deformation caused by heat-press molding for obtaining a laminated glass having an intermediate layer and a support. A film which has at least one thermoplastic resin layer, and which is characterized in that: S (T)% is the shrinkage rate at a temperature T DEG C in a thermal shrinkage curve; and when the X direction is the direction in which S (150) is the largest among any one direction in a plane parallel to the film surface and each direction rotating from the direction to 180 degrees at an interval of 5 degrees along the in-plane direction parallel to the film surface, 0.50 < = S (150)-S (100) and 0.00 < = S (120)-S (100) < = 0.40 are satisfied in the X direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film suitable for laminated glass and the like, a method for producing the film, a laminated structure using the film, laminated glass, and an automobile. Background Art

[0002] There are many products with high requirements for the appearance design of the shell, such as mobile phones, frames of personal computers, electrical appliances, furniture, and automobiles. In addition, the requirements for the appearance design of these products have also increased in recent years. As methods for imparting appearance design to these products, there are known methods such as coating or printing, pasting colored films, and transferring the printed surface of the printed film to a substrate. In addition, in these products, in addition to the requirements for appearance design, the requirements for the functionality of the shell are also increased. For example, there is a known method for imparting functions such as heat absorption, gas barrier properties, adhesion, and conductivity to the shell substrate via a heating process.

[0003] In recent years, due to the restrictions on carbon dioxide emission for environmental protection, heat-blocking glass that can suppress the inflow of heat from the outside, especially from sunlight in summer, has attracted attention, and attempts have been made to use it in vehicles such as cars and trains, and window glass for buildings. As an example of such heat-blocking glass, there are substrates that use an interlayer film to block heat by assembling a substrate having a heat-absorbing material layer into a laminated glass, and substrates that use an interlayer film to form a metal film by sputtering or the like as a laminated glass to reflect and block heat.

[0004] Such heat-cut glass is usually used in places that contact human eyes, so appearance becomes important. Furthermore, before the processing step of the heat-cut glass, it is necessary to perform processing such as lamination or sputtering of functional layers on the substrate such as a film, so the substrate such as the film also needs to have suitability in the processing step. For example, in the molding of laminated glass containing a substrate such as a film, it is known that there is a problem that the film produces uneven deformation in a concave and convex shape during molding due to uneven pressing caused by uneven thickness of the intermediate film used for lamination with the glass as a support body, and the difference in thermal shrinkage stress with the intermediate film, thereby damaging the appearance. As the cause of the above-mentioned problem, for example, it is known that there is a difference in thermal shrinkage rate between the intermediate film and the film under processing conditions, and a scheme for controlling the thermal shrinkage rate has been proposed (for example, Patent Documents 1 and 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2013 / 137288

[0008] Patent Document 2: Japanese Patent Application Publication No. 2012-30563 Summary of the invention

[0009] Inventions should solve problems

[0010] However, the proposals of Patent Documents 1 and 2 are proposals specifically for suppressing unevenness after laminated glass (improving appearance), and are not sufficiently adaptable to a process involving heating of a substrate such as a film before laminated glass. The subject of the present invention is to provide a film that is highly adaptable to a process of laminating a functional layer accompanied by heating, and can suppress uneven deformation caused by heat-pressing molding for obtaining laminated glass having an intermediate layer and a support.

[0011] Solution

[0012] In the manufacture of laminated glass, the laminated support (glass), interlayer and film are heated and pressurized in order to improve the closeness between each component. In this process, due to the uneven thickness of the interlayer or the difference in thermal shrinkage stress between the interlayer and the film, the film produces a concavoconvex deformation, which then produces scattering or diffuse reflection of light, so the appearance of the laminated glass deteriorates. At this time, since the support is almost not deformed, the shape of the interlayer will not change due to the support. Therefore, if it is possible to use a film that is difficult to produce concavoconvex, the problem of poor appearance of laminated glass can be solved. Then, when using a film (laminated structure) of a process of laminating a functional layer with heating, the support, the interlayer and the film are laminated and formed, the control of the thermal shrinkage stress of the laminated structure or the film constituting it becomes important.

[0013] The poor appearance of laminated glass obtained by heat-pressing a support, an interlayer, and a film is believed to be caused by uneven deformation of the film, and the inventors have studied how to eliminate the unevenness, resulting in the present invention.

[0014] In order to solve the above-mentioned problems, the present invention has the following means.

[0015] [1]. A film having at least one thermoplastic resin layer,

[0016] When the shrinkage rate at temperature T°C in the heat shrinkage curve is defined as S(T)%, and the direction in which S(150) is the largest in any direction in a plane parallel to the film plane and in each direction rotated from the direction in the plane parallel to the film plane at intervals of 5° to 180° is defined as the X direction, the following conditions are satisfied in the X direction:

[0017] 0.50≤|S(150)-S(100)|, and

[0018] 0.00≤|S(120)-S(100)|≤0.40.

[0019] [2] The film according to [1], wherein the shrinkage start temperature in the heat shrinkage curve in the X direction is 110° C. or higher and 170° C. or lower.

[0020] [3] For the film described in [1] or [2], in the X direction, the average shrinkage rate from 100°C to 120°C in the heat shrinkage curve is greater than -0.40% and less than 0.50%, and the absolute value of the average change rate of the shrinkage rate from 120°C to 150°C is greater than 0.04% / °C.

[0021] [4] The film according to any one of [1] to [3], which has a structure in which 51 or more thermoplastic resin layers are stacked.

[0022] [5] The film according to any one of [1] to [4], wherein when two thermoplastic resin layers having different main components are respectively provided as the A1 layer and the B1 layer, the film comprises the A1 layer and the B1 layer.

[0023] [6] A film as described in any one of [1] to [4], which has a regular arrangement formed by the A2 layer, the B2 layer and the C2 layer when three thermoplastic resin layers having different main components are respectively set as the A2 layer, the B2 layer and the C2 layer.

[0024] [7] The film according to any one of [1] to [6], wherein at least one of the thermoplastic resin layers is a polyester resin layer.

[0025] 8. A method for producing a thin film, which is the method for producing a thin film as described in any one of [1] to [7], comprising a re-annealing step of heat-treating a sheet satisfying 0.50≤|S(150)-S(100)| at a temperature of not less than 110°C and less than 140°C.

[0026] [9]. The method for producing a thin film as described in [8], wherein the sheet satisfies 0.40<|S(120)-S(100)|.

[0027]

[10] . A laminated structure comprising a functional layer laminated on at least one surface of the film described in any one of [1] to [7].

[0028]

[11] . In the laminated structure described in

[10] , the functional layer is a conductive layer.

[0029]

[12] The laminated structure as described in

[10] or

[11] , wherein the functional layer has a plurality of layers, at least one of which is a second film having an absolute value of shrinkage at 120°C of 0.20% or less.

[0030]

[13] The laminated structure as described in

[12] , when the orientation angle of the film is set to θb and the orientation angle of the second film is set to θf, the laminated structure is bonded in a manner such that |θb-θf|≤30°.

[0031]

[14] A laminate structure as described in any one of

[10] to

[13] , having the functional layers on both sides, wherein one functional layer is a conductive layer and the other functional layer is a second film having an absolute value of shrinkage at 120°C of not more than 0.20%.

[0032]

[15] The stacked structure as described in any one of

[10] to

[14] has at least one reflection band with a reflectivity of 30% or more and continuous over a wavelength range of 20 nm or more in a reflectivity curve measured from at least one surface.

[0033]

[16] . In the laminated structure described in

[15] , the reflection band exists in the wavelength range of 850 nm to 1200 nm.

[0034]

[17] . The laminated structure according to any one of

[10] to

[16] , wherein the visible light transmittance is 70% or more.

[0035]

[18] . A method for producing a stacked structure, which is the method for producing a stacked structure according to any one of

[11] to

[17] , comprising a step of performing a heat treatment at a temperature of not less than 100°C and less than 130°C when forming the conductive layer.

[0036]

[19] . A laminated glass comprising, in this order, glass 1, an intermediate layer 1, the laminate structure according to any one of

[11] to

[17] , an intermediate layer 2, and glass 2.

[0037]

[20] . The laminated glass as described in

[19] , wherein the glass 1 is located on the sunlight incident side, and the conductive layer of the laminated structure is located on the intermediate layer 1 side.

[0038]

[21] . A car comprising the laminated glass described in

[19] , wherein the laminated glass exhibits optical function or thermal function by energizing the conductive layer of the laminated glass.

[0039] Effects of the Invention

[0040] The present invention is a film having excellent processing suitability before and after processing into laminated glass or the like. By using the film of the present invention, laminated glass having excellent appearance and design properties can be obtained. DETAILED DESCRIPTION

[0041] The present invention is described in detail below, but the present invention is not limited to the specific implementation modes including the following embodiments, and various changes that can achieve the purpose of the invention and do not depart from the spirit of the invention are all within the scope of the present invention.

[0042] The film of the present invention needs to have at least one thermoplastic resin layer, and when the shrinkage rate at temperature T°C in the heat shrinkage curve is set as S(T)%, and the direction in which S(150) is the largest in any direction in a plane parallel to the film surface and in each direction rotated from the direction at intervals of 5° to 180° along the plane direction parallel to the film surface is set as the X direction, the following conditions are satisfied in the X direction:

[0043] 0.50≤|S(150)-S(100)|, and

[0044] 0.00≤|S(120)-S(100)|≤0.40.

[0045] Here, the thermoplastic resin layer refers to a layer containing a thermoplastic resin as a main component, that is, a layer containing a total of more than 50% by mass and 100% by mass or less of the thermoplastic resin when the entire layer is 100% by mass.

[0046] Representative thermoplastic resins for forming the thermoplastic resin layer of the film of the present invention are shown below, but the thermoplastic resins used in the present invention are not limited to those shown below. The thermoplastic resin layer of the film of the present invention can use, for example, polyolefin resins represented by polyethylene, polypropylene, poly(1-butene), poly(4-methylpentene), polyisobutylene, polyisoprene, polybutadiene, polyvinylcyclohexane, polystyrene, poly(α-methylstyrene), poly(p-methylstyrene), polynorbornene, polycyclopentene, etc., polyamide resins represented by nylon 6, nylon 11, nylon 12, nylon 66, etc., ethylene / propylene copolymers, ethylene / vinylcyclohexane copolymers, ethylene / vinylcyclohexene copolymers, ethylene / alkyl acrylate copolymers, ethylene / acrylate methacrylate copolymers, ethylene / norbornene copolymers, ethylene / vinyl acetate copolymers, propylene / butadiene copolymers, isobutylene / isoprene copolymers, vinyl chloride / vinyl acetate copolymers, etc. Copolymer resins of polyol-based monomers, acrylic resins represented by polyacrylate, polyisobutyl methacrylate, polymethacrylate, polymethyl methacrylate, polybutyl acrylate, polyacrylamide, polyacrylonitrile, etc., polyester resins represented by polyethylene terephthalate, polytrimethylene terephthalate, polybutylene terephthalate, polyethylene 2,6-naphthalate, etc., biodegradable resins represented by polylactic acid, polybutyl succinate, etc., and polyvinylidene chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl butyral, polyacetal, polyglycolic acid, polycarbonate, polyketone, polyether sulfone, polyether ether ketone, modified polyphenylene ether, polyphenylene sulfide, polyetherimide, polyimide, polysiloxane, tetrafluoroethylene resin, trifluoroethylene resin, chlorotrifluoroethylene resin, tetrafluoroethylene / hexafluoropropylene copolymer, polyvinylidene fluoride, etc.

[0047] In each thermoplastic resin layer, these thermoplastic resins may be used alone, or two or more thermoplastic resins may be used as a mixture or alloy. By implementing the mixing or alloying, in addition to obtaining physical / chemical properties that cannot be obtained from one thermoplastic resin, in the case of stacking thermoplastic resin layers with greatly different skeleton structures, if a component common to the polymer skeleton structure contained in the thermoplastic resin layer on the opposite side can be given to the thermoplastic resin layer on one side of the adjacent thermoplastic resin layers as a copolymer component, the interlayer adhesion of the interface can be improved.

[0048] In each thermoplastic resin layer constituting the film of the present invention, from the viewpoint of strength, heat resistance, transparency, and rheological properties of laminability, the thermoplastic resin constituting the thermoplastic resin layer is particularly preferably selected from polyolefin resins, polyester resins, acrylic resins, polycarbonate resins, and polyamide resins. Among them, from the viewpoint above, polyester resins are more preferably used, and at least one layer of the thermoplastic resin layer is more preferably a polyester resin layer. More preferably, a polyester resin is obtained by polymerizing a monomer having aromatic dicarboxylic acid or aliphatic dicarboxylic acid and a diol as main components.

[0049] Here, as aromatic dicarboxylic acids, for example, terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-diphenyl sulfone dicarboxylic acid, etc. can be listed. As aliphatic dicarboxylic acids, for example, adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexane dicarboxylic acid and their ester derivatives can be listed. Among them, terephthalic acid and 2,6-naphthalene dicarboxylic acid can be preferably listed. In addition, these acid components can be used alone or in combination of two or more, and hydroxy acids such as hydroxybenzoic acid can be partially copolymerized.

[0050] In addition, as the diol component, for example, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, neopentyl glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbide, spiroglycol, etc. can be listed. Among them, ethylene glycol is preferably used. These diol components can be used alone or in combination of two or more.

[0051] In each thermoplastic resin layer constituting the film of the present invention, among the above-mentioned polyester resins, it is particularly preferable to use a polyester resin selected from polyethylene terephthalate and its copolymers, polyethylene naphthalate and its copolymers, polybutylene terephthalate and its copolymers, polybutylene naphthalate and its copolymers, poly(1,6-hexane terephthalate) and its copolymers, and poly(1,6-hexane naphthalate) and its copolymers.

[0052] The film of the present invention preferably has a structure of more than 51 layers of thermoplastic resin layers stacked. By stacking thermoplastic resins, the film can be given a function that cannot be obtained by only one layer of thermoplastic resin. For example, if it is a function such as reflection of light, the more the number of layers is, the more the function can be improved based on the principle of interference reflection. From the above viewpoint, the number of thermoplastic resin layers is more preferably more than 401 layers. By increasing the number of layers, the interference function from stacking can be improved, for example, the hot line cut-off performance can be improved. From the viewpoint of the large-scale stacking device, the upper limit is about 5001 layers. In addition, the film with the structure of more than 51 layers of thermoplastic resin layers stacked is used as a laminated film.

[0053] By making the thin film of the present invention into a laminated film as described above, it is easy to show the function of selectively reflecting light of a specific wavelength band by interference reflection, the function of reflecting specific polarized light, etc., according to the relationship between the difference in refractive index of each layer and the layer thickness. For example, in the case of forming a laminated film having the function of reflecting infrared rays, by sandwiching the laminated film between two sheets of glass, a laminated glass with high heat insulation performance can also be formed. Alternatively, in the case of forming a laminated film having the function of reflecting specific polarized light, by sandwiching the laminated film between two sheets of glass, a glass component suitable for a display device that displays images with specific polarized light can also be formed.

[0054] The film of the present invention preferably has an A1 layer and a B1 layer when two thermoplastic resin layers having different main components are respectively set as an A1 layer and a B1 layer. In addition, the film of the present invention preferably has a regular arrangement consisting of an A2 layer, a B2 layer, and a C2 layer when three thermoplastic resin layers having different main components are respectively set as an A2 layer, a B2 layer, and a C2 layer.

[0055] In the film of the present invention, "main component" refers to a component containing more than 50% by mass and less than 100% by mass in a layer. As a secondary component that is not a main component, low molecular weight organic components such as inorganic components or thermoplastic resins are equivalent to secondary components. As a specific example, light absorbers (ultraviolet absorbers, dyes, pigments, heat absorbers), antioxidants, light stabilizers, matting agents, heat stabilizers, weather stabilizers, organic lubricants, fillers, antistatic agents, nucleators, flame retardants, etc. can be listed. These secondary components can be freely added in each layer to the extent that the original physical properties and functions of the film are not damaged.

[0056] Among these secondary components, depending on the type of thermoplastic resin constituting each thermoplastic resin layer, sometimes it absorbs high-energy ultraviolet rays and promotes degradation accordingly. Therefore, in order to make its reaction competitive and suppress light degradation, it is preferred to contain an ultraviolet absorber. Furthermore, the light absorber such as the ultraviolet absorber itself is sometimes affected by degradation caused by heat or oxygen, light degradation caused by ultraviolet rays or reaction with oxygen, etc. in the resin extrusion process in the manufacture of the film. Therefore, to the extent that the original physical properties and functions of the film are not damaged, in the layer containing the thermoplastic resin that may be degraded, an antioxidant can be added to the former, and a light stabilizer and a matting agent can be added as additives to the latter.

[0057] In the film of the present invention, the thermoplastic resin layer is "different" which means at least one of the following: (1) different composition, (2) different glass transition temperature or melting point in differential scanning calorimetry (DSC), (3) different contrast of the dyed image when observing the cross section under transmission electron microscopy (TEM).

[0058] "Different compositions" means that the conditions for being regarded as "same compositions" shown below are not met. "Same compositions" means that the repeating units of the chemical structures of the thermoplastic resins constituting the respective thermoplastic resin layers share 95 mol% or more and 100 mol% or less of the components when comparing the constituent components of the respective thermoplastic resin layers.

[0059] For example, in the former, if it is polyethylene terephthalate, it has a constituent unit (ethylene terephthalate unit) formed by ester bonding of ethylene glycol units and terephthalic acid units as the main constituent unit. However, if the resins constituting the layers have a common chemical structure of an ethylene terephthalate skeleton but the amount of the copolymer component exceeds 5 mol%, such as a layer composed of homopolyethylene terephthalate and a layer composed of polyethylene terephthalate copolymerized with 10 mol% of isophthalic acid, the two are considered to have different compositions. In addition, in the latter, if the same constituent component is the main component but the components exceeding 5 mol% are different from each other, such as a layer composed of homopolyethylene terephthalate and a layer containing 90% by mass of homopolyethylene terephthalate and the remaining 10% by mass of other components, the two are also considered to have different compositions. The repeating unit structure of the specific composition / chemical structure of each thermoplastic resin layer can be determined by the method described in the layer structure of the measurement method described later, and then the thermoplastic resin layer is scraped out, or the layer is scraped off to expose the outermost layer, thereby using infrared spectroscopy (FT-IR method or nano-IR method), gas chromatography / mass spectrometry (GC-MS), nuclear magnetic resonance device (NMR), etc.

[0060] On the other hand, when it is difficult to identify the composition by the above method after extracting each thermoplastic resin layer, the thermoplastic resin layers constituting the laminated film show different melting points and / or glass transition temperatures in differential scanning calorimetry (DSC), and can be judged as "different". In addition, in the present invention, the so-called different melting points and different glass transition temperatures refer to the difference between the melting point and the glass transition temperature of 0.1°C or more, preferably 2°C or more. On the other hand, sometimes the thermoplastic resin layer does not show the glass transition temperature and the melting point, but when the thermoplastic resin layer on one side shows the glass transition temperature or the melting point and the thermoplastic resin layer on the other side does not show it, the temperature difference cannot be calculated, but it can be interpreted that the thermoplastic resin layers are different. In addition, in the measurement using DSC in the present invention, the measurement temperature range can be set to be above 25°C and below 300°C, and the method of JIS-K-7122 (1987) can be used.

[0061] In the above two methods, it is necessary to separate the corresponding thermoplastic resin layer from the film for analysis, but it is sometimes difficult to separate the layer. Therefore, in the present invention, for simplicity, when the layer interface caused by the contrast difference can be identified in the cross-sectional image observed by transmission electron microscope observation, and when it can be confirmed by the method described in the layer interface (contrast difference) in the measurement method described later that the difference in the average brightness of two adjacent layers is larger than any of the standard deviations of the brightness in each layer of the adjacent thermoplastic resin layer, the contrast of the image after dyeing is considered to be different, and the composition of the adjacent thermoplastic resin layer is judged to be "different".

[0062] This contrast difference is caused by the difference in electron beam scattering, crystal diffraction, etc. between thermoplastic resin layers. Therefore, when the composition of the thermoplastic resin layer is different according to the above-mentioned criteria, the crystallinity or electron density state is different, and the electron staining state is also different according to the type of thermoplastic resin constituting each thermoplastic resin layer and the copolymerization amount of the combined thermoplastic resin. That is, in the case of thermoplastic resin layers with different compositions, it can be seen in the cross-sectional image of the laminated film that each thermoplastic resin layer has a layer structure with a contrast difference. In addition, the presence or absence of a contrast difference can be evaluated by the method described later.

[0063] The film of the present invention preferably has an A1 layer and a B1 layer when two thermoplastic resin layers with different main components are respectively set as an A1 layer and a B1 layer. From the viewpoint of interlayer adhesion and easy to realize a laminated structure with high precision, the above two thermoplastic resin layers preferably contain thermoplastic resins with the same basic skeleton. The basic skeleton is the most repeating unit contained in the molecular chain, for example, in the case of polyethylene terephthalate, it is an ethylene terephthalate unit, and in the case of polyethylene, it is an ethylene unit. In addition, in such a mode, in the case of forming a structure in which more than 51 layers of thermoplastic resin layers are laminated, it is preferred to have a structure in which an A1 layer and a B1 layer are alternately laminated.

[0064] As a preferred combination of thermoplastic resins used in the A1 layer and the B1 layer of the film of the present invention, it is preferred that the main component thermoplastic resin of the A1 layer and the main component thermoplastic resin of the B1 layer are a combination that can provide the same basic skeleton. If the thermoplastic resins as the main components of each layer contain the same basic skeleton, the lamination accuracy is high, and interlayer delamination is less likely to occur at the lamination interface.

[0065] In order to make the thermoplastic resin with the same basic skeleton have different properties, it is preferred to set one side as a copolymer, or to set both as copolymers in a form in which the types or copolymerization amounts of the copolymerized units are different. As an example of the former, for example, the thermoplastic resin on one side is homopolyethylene terephthalate, and the thermoplastic resin on the other side is a form of a resin consisting of ethylene terephthalate units and repeating units with other ester bonds. As the proportion of adding other repeating units (sometimes referred to as copolymerization amount), it is preferably more than 5mol% from the necessity of obtaining different properties. On the other hand, since the difference in the adhesion and thermal flow characteristics between the layers is small, the thickness accuracy and thickness uniformity of each layer are excellent, so it is preferably less than 50mol%. More preferably, it is more than 10 mol% and less than 45 mol%. In addition, as an example of the latter, for example, a thermoplastic resin can be listed, which is a resin consisting of ethylene terephthalate units and repeating units with other ester bonds, and its copolymerization amounts are different from each other. In addition, it is also preferred that the A1 layer and the B1 layer are mixed or alloyed with a variety of thermoplastic resins respectively. By mixing or alloying a plurality of thermoplastic resins, it is possible to obtain properties that cannot be obtained with only one thermoplastic resin.

[0066] In addition, the preferred combination of thermoplastic resins used as the main components of the A1 layer and the B1 layer of the film of the present invention is preferably such that the difference in glass transition temperature of each thermoplastic resin is 20° C. or less. By making the difference in glass transition temperature 20° C. or less, the thickness uniformity during the manufacture of the laminated film becomes good, and the reflection characteristics become more uniform. In addition, the occurrence of overstretching can also be reduced during film molding.

[0067] In the case where the film of the present invention has a layer structure in which the A1 layer and the B1 layer are alternately stacked and the A1 layer is arranged as the outermost layer on both sides, when the difference in glass transition temperature between the main component thermoplastic resin of the A1 layer (thermoplastic resin A1) and the main component thermoplastic resin of the B1 layer (thermoplastic resin B1) is greater than 5°C, it is more preferred that the glass transition temperature of the thermoplastic resin A1 is higher than the glass transition temperature of the thermoplastic resin B1. By making the glass transition temperature of the A1 layer as the outermost layer relatively high, the adhesion to the roll or the clamp during longitudinal stretching or transverse stretching is reduced, and the deterioration of the appearance quality can be suppressed.

[0068] The film of the present invention preferably has a difference in the in-plane average refractive index between the A layer and the B layer of 0.03 or more. More preferably, it is 0.05 or more, and further preferably 0.10 or more. When the difference in the in-plane average refractive index between the A layer and the B layer is 0.03 or more, sufficient reflectivity can be obtained, so for example, the heat-ray cutoff performance is improved. As a method for setting the difference in the in-plane average refractive index between the A layer and the B layer to the above range, a method of making one side of the resin A and B crystalline and the other side a non-crystalline form can be cited. The crystallinity mentioned here refers to a melting enthalpy of 10 J / g or more in differential scanning calorimetry (DSC). On the other hand, the so-called non-crystalline also refers to a melting enthalpy of less than 10 J / g. In the case of such a resin combination, the in-plane refractive index difference can be easily set in the stretching and heat treatment steps in the manufacture of the film. In addition, in the case of amorphous resins, since the refractive index usually does not change due to the stretching and heat treatment steps in the manufacture of the film, the refractive index can also be measured by pressing the resin into a sheet after vacuum drying as needed. The in-plane refractive index refers to the average value of the refractive index in the X direction and the Y direction (described later) (the details of the determination method of each direction and the measurement method of the refractive index are described later).

[0069] As an example of a resin combination for satisfying the above conditions, in the film of the present invention, it is preferred that the A1 layer has polyethylene terephthalate or polyethylene naphthalate as the main component, and the B1 layer has a polyester having the same basic skeleton as the main component of the A1 layer and containing spiroglycol as the main component. The polyester containing spiroglycol refers to a copolyester copolymerized with spiroglycol, or a polyester mixed with a homopolyester and a copolyester copolymerized with spiroglycol. The polyester containing spiroglycol is not easy to be overstretched during molding and is not easy to peel between layers because the glass transition temperature difference between the polyester containing spiroglycol and polyethylene terephthalate or polyethylene naphthalate is small, so it is preferred. From the above viewpoint, it is more preferred that the A1 layer has polyethylene terephthalate or polyethylene naphthalate as the main component, and the B1 layer has a polyester having the same basic skeleton as the main component of the A1 layer and containing spiroglycol and cyclohexanedicarboxylic acid as the main component. If the main component of the B1 layer is a polyester containing spiroglycol and cyclohexanedicarboxylic acid, the difference in in-plane refractive index with polyethylene terephthalate and polyethylene naphthalate becomes large, so it is easy to obtain a high reflectivity by alternately laminating the A1 layer and the B1 layer. In addition, such a polyester has a small difference in glass transition temperature with polyethylene terephthalate and polyethylene naphthalate, and has excellent adhesion. Therefore, it is not easy to be overstretched during film molding, and the interlayer delamination between the A1 layer and the B1 layer can also be reduced.

[0070] The copolymerization amount of the polyester containing spiroglycol and cyclohexanedicarboxylic acid is preferably 5 mol% to 30 mol% of spiroglycol and 5 mol% to 30 mol% of cyclohexanedicarboxylic acid. In addition, the copolymerization amount of the polyester containing spiroglycol is preferably 5 mol% or more and less than 50 mol%.

[0071] In addition, when the film of the present invention has a layer structure in which the A1 layer and the B1 layer are alternately stacked and the A1 layer is arranged as the outermost layer on both sides, it is preferred that the main component of the A1 layer is a crystalline polyester and the main component of the A2 layer is an amorphous polyester. In the case of such a resin combination, as described above, in addition to being able to easily set the in-plane refractive index difference in the stretching and heat treatment steps in the production of the film, it is also possible to relax the orientation by heat treatment at a temperature much higher than the glass transition temperature of the amorphous polyester and below the melting point of the crystalline polyester.

[0072] In addition, it is preferred that the A1 layer contains the main component resin of the B1 layer as a small component, the B1 layer contains the main component resin of the A1 layer as a small component, and a combination of the above two. In this way, by mixing a small amount of the main component resins of the A1 layer and the B1 layer in one or both of them, high-precision lamination, improvement of interlayer adhesion, and improvement of stretchability during film formation can be obtained. As for the mixing ratio, when the entire layer is set to 100% by mass, it is preferably in the range of 5% to 30% by mass.

[0073] In addition, the film of the present invention preferably has a regular arrangement consisting of the A2 layer, the B2 layer and the C2 layer when the three thermoplastic resin layers with different main components are respectively set as the A2 layer, the B2 layer and the C2 layer. Here, the so-called regular arrangement refers to a laminated structure formed by stacking the "different" three thermoplastic resin layers according to a certain regular arrangement according to the above definition. At this time, the three different thermoplastic resin layers can be formed by thermoplastic resins with mutually different skeleton structures, and the thermoplastic resins with two skeleton structures can also be used to design the different mixing ratios or copolymerization amounts of the three thermoplastic resin layers. Later in this specification, for convenience, different thermoplastic resin layers are observed from the outermost surface of the film, and are defined as the A2 layer, the B2 layer, and the C2 layer in alphabetical order from the first appearance, and the thermoplastic resins as the main components of each thermoplastic resin layer are defined as thermoplastic resin A2, thermoplastic resin B2, and thermoplastic resin C2.

[0074] When different thermoplastic resin layers are defined as A2 layer, B2 layer, and C2 layer in the order of configuration from the outermost surface of the laminated film, the regular arrangement of the film of the present invention can be listed, for example, (ABC)x, (ABCB)x, (ABAC)x, (ABCAB)x, (ABCAC)x, (ABABC)x, (ABCBCB)x (the regular arrangement form is indicated in brackets, and x is a natural number indicating the number of repetitions. A, B, and C represent A2 layer, B layer, and C2 layer, respectively. In addition, the same symbols are sometimes used in the following description of the regular arrangement formed by A2 layer, B layer, and C2 layer.) etc. Among them, in order to make the film formed by thermoplastic resins with different physical / chemical properties such as skeleton structure, viscoelasticity, and viscosity characteristics maintain the laminated structure for a long time without interfacial delamination and without damaging the required functions, it is necessary to study the combination of thermoplastic resin layers with good compatibility (compatibility, surface free energy, etc.) for adjacent thermoplastic resin layers forming the interface of different thermoplastic resin layers contained in the film.

[0075] Therefore, in order to make the resin design of the whole film uncomplicated, it is preferred that the combination of the interface formed by the adjacent thermoplastic resin layers has few types. Specifically, the interface formed by 3 different thermoplastic resin layers can list 3 kinds of A2-B2 interface, B2-C2 interface, and C2-A2 interface, but in the above-mentioned regular arrangement, (ABCB)x and (ABCBCB)x only have 2 kinds of A2-B2 interface and B2-C2 interface, which is preferred. In such a way, the resin design can be carried out in a way that is not easy to produce the interlayer peeling of A2 layer and B2 layer, B2 layer and C2 layer, and the combination of A2 layer and C2 layer can also be considered less.

[0076] The film of the present invention, when the shrinkage rate at temperature T°C in the heat shrinkage curve is set as S(T)%, and the direction in which S(150) is the maximum in any direction in the plane parallel to the film surface and in each direction rotated from the direction along the plane parallel to the film surface at intervals of 5° to 180° is set as the X direction, it is necessary to satisfy the following in the X direction: 0.50≤|S(150)-S(100)|, and 0.00≤|S(120)-S(100)|≤0.40. The heat shrinkage curve mentioned here is a curve measured by thermomechanical analysis under the conditions of temperature of 25°C to 200°C and heating rate of 10°C / min, with the length at 25°C as the reference, positive indicates shrinkage, and negative indicates expansion. It is more preferred that 0.50≤|S(150)-S(100)|≤2.60 and 0.00≤|S(120)-S(100)|≤0.30 be satisfied, and it is still more preferred that 1.00≤|S(150)-S(100)|≤2.60 and 0.00≤|S(120)-S(100)|≤0.20 be satisfied, and it is particularly preferred that 1.00≤|S(150)-S(100)|≤2.60 and 0.00≤|S(120)-S(100)|≤0.19 be satisfied.

[0077] By satisfying 0.50≤S(150)-S(100) in the X direction of the film, the uneven pressing caused by the uneven thickness of the intermediate layer or the concave-convex deformation of the film caused by the difference in thermal shrinkage stress between the intermediate layer and the film when making a laminated glass or other molded body can be suppressed, thereby improving the appearance of the laminated glass when it is formed. Furthermore, by satisfying 0.00≤|S(120)-S(100)|≤0.40 in the X direction of the film, in the heating process when the functional layer is laminated on the film, curling caused by the deformation of the film or the difference in shrinkage rate with the functional layer will not occur, and the processing can be efficient and good. In addition, when the direction rotated 90° from the X direction parallel to the film surface is set to the Y direction, the ratio of the shrinkage rate in the X direction to the Y direction is preferably 0.5 or more and 2.0 or less. If the balance of the shrinkage rate in the X direction and the Y direction is poor, wrinkles may be generated during processing, but by good balance, a laminated glass with fewer wrinkles can be obtained.

[0078] The film of the present invention preferably has a shrinkage start temperature of the heat shrinkage curve in the X direction of 110°C or more and 170°C or less. Here, the shrinkage start temperature in the heat shrinkage curve refers to the temperature at which the shrinkage rate exceeds 0% when the shrinkage rate is based on 25°C in the heat shrinkage curve of the film measured at a temperature of 25°C to 200°C and a heating rate of 10°C / min. By setting the shrinkage start temperature to be above 110°C, the deformation of the film and the curling caused by the difference in shrinkage rate with the functional layer can be reduced in the heating process when the functional layer is laminated. In addition, by setting the shrinkage start temperature to be below 170°C, the uneven pressing caused by the uneven thickness of the intermediate layer when making a molded body such as laminated glass, and the occurrence of concave-convex deformation of the film caused by the difference in thermal shrinkage stress between the intermediate layer and the film can be suppressed. From the above viewpoint, the shrinkage start temperature of the heat shrinkage curve in the X direction is more preferably above 110°C and below 150°C, and more preferably above 110°C and less than 140°C.

[0079] In the film of the present invention, in the X direction, the average shrinkage rate from 100°C to 120°C in the heat shrinkage curve is preferably -0.40% to 0.50%, and the absolute value of the average change rate of the shrinkage rate from 120°C to 150°C is 0.04% / °C or more. Here, the "average of the shrinkage rate from 100°C to 120°C in the heat shrinkage curve" refers to the average value of all measured values ​​from 100°C to 120°C in the heat shrinkage curve, and the "absolute value of the average change rate of the shrinkage rate from 120°C to 150°C" refers to the absolute value of the value obtained by dividing the difference between S(150) and S(120) by the temperature difference of 30°C between 120°C and 150°C. By adopting this method, the film has less curling and the like caused by the difference in shrinkage rate with the functional layer during the heating process when the functional layer is laminated, and the concavo-convex deformation in the subsequent processing for obtaining a molded body such as laminated glass is reduced.

[0080] A specific example of a method for making the film of the present invention have the properties of 0.50≤|S(150)-S(100)| and 0.00≤|S(120)-S(100)|≤0.40 in the above-mentioned X direction is described below, but the explanation is not limited to this method.

[0081] As a method for making the film of the present invention have the characteristics of 0.50≤|S(150)-S(100)| and 0.00≤|S(120)-S(100)|≤0.40 in the X direction, there can be cited a method of subjecting a sheet satisfying 0.50≤|S(150)-S(100)| to re-annealing at a temperature of 100° C. to 140° C., preferably 110° C. to less than 140° C., and more preferably 125° C. to less than 140° C. In this case, it is preferable to use a sheet satisfying 1.00≤|S(150)-S(100)|, more preferably 1.50≤|S(150)-S(100)|, and even more preferably 1.50≤|S(150)-S(100)|≤3.50. By satisfying |S(150)-S(100)|≤3.50, shrinkage of the sheet during reannealing is reduced, and the occurrence of scratches and the like can be reduced.

[0082] In addition, it is preferred that the sheet satisfies 0.40<|S(120)-S(100)|. The method for obtaining the sheet will be described later. By using a sheet that satisfies 0.40<|S(120)-S(100)|, it is easy to satisfy 0.50≤|S(150)-S(100)| and adjust |S(150)-S(100)| to the above-mentioned more preferred range. In this case, it is more preferred to use a sheet that satisfies 0.45<|S(120)-S(100)|<0.85. By satisfying |S(120)-S(100)|<0.85, the shrinkage of the sheet during the re-annealing treatment is reduced, and the occurrence of scratches and the like can be reduced.

[0083] Here, the so-called sheet may be an unoriented sheet that has been sheeted by a melt extrusion process and a casting process, or a biaxially oriented sheet that has been biaxially stretched to form an unoriented sheet. Biaxial stretching refers to stretching in the length direction and the width direction. Stretching can be performed in two directions in sequence or simultaneously. In addition, re-stretching can be performed in the length direction and / or the width direction as required. Here, the so-called length direction refers to the moving direction of the sheet or film (the winding direction of the film when it becomes a film roll), and the so-called width direction refers to the direction orthogonal to the length direction in the film surface. In particular, in the present invention, from the viewpoint of isotropic mechanical properties such as heat shrinkage behavior, it is preferred to use a biaxially oriented sheet.

[0084] Next, a preferred method for producing a biaxially oriented sheet satisfying 0.50≤|S(150)-S(100)| suitable for the film of the present invention will be described below using a sequential biaxial stretching method as an example, but the present invention is not limited to such an example.

[0085] First, the thermoplastic resin constituting each thermoplastic resin layer of the sheet is prepared in the form of particles or the like. Here, in the case where the amorphous polyester and the crystalline polyester are in the form of an alloy, it is preferred to prepare in advance particles kneaded by a twin-screw extruder or the like. In addition, the dispersion state of the crystalline polyester can be achieved by controlling the selection of the screw of the twin-screw extruder, the discharge amount, the screw speed, the kneading temperature, etc., and further, it can be achieved by adding a compatibilizer such as a polyester elastomer. In this way, by preparing kneaded particles in advance by a twin-screw extruder or the like, the dispersion state and domain size of the crystalline polyester in the amorphous polyester can be controlled.

[0086] Then, the particles are dried in hot air or under vacuum as needed, and then provided to different extruders. After the particles are heated and melted to above the melting point or 250-330°C in each extruder, the extrusion amount of the resin is uniformed by a gear pump, etc., and foreign matter or modified resins are removed from the molten resin by a filter, etc. Then, it is formed into a sheet with a die head and discharged, and cooled and solidified on a cooling body such as a casting drum to obtain an unoriented sheet. At this time, it is preferred to use a linear, strip-shaped, needle-shaped or knife-shaped electrode, and utilize electrostatic force to make the molten sheet close to a cooling body such as a casting drum and quench and solidify. In addition, as a method for making the molten sheet close to the cooling body, it is preferred to blow air from a slit-shaped, point-shaped, or planar device to make the molten sheet close to the cooling body, or to use a clamping roller to make the molten sheet close to the cooling body. At this time, the surface temperature of the casting drum is preferably 20-50°C.

[0087] In addition, when making a sheet consisting of multiple thermoplastic resin layers, multiple resins are sent out from different flow paths using more than 2 extruders and sent into a multilayer laminating device. As a multilayer laminating device, a multi-manifold die head, a feed block, a static mixer, etc. can be used. In particular, in order to effectively obtain the preferred layer structure of the film of the present invention, it is preferred to use a feed block containing at least 2 or more independent components with a large number of fine slits. If such a feed block is used, since the device will not be extremely large-scale, it is possible to suppress the generation of foreign matter caused by thermal degradation, and high-precision lamination can be performed even when the number of laminations is extremely large. In addition, compared with the prior art, the lamination accuracy in the width direction is also significantly improved, and it is also easy to form an arbitrary layer thickness structure. The device can adjust the thickness of each layer with the shape (length, width) of the slit, so it is easy to achieve an arbitrary layer thickness. The molten multilayer laminate formed into the desired layer structure is guided to the die head, and an unoriented sheet is obtained in the same manner as above.

[0088] Next, the obtained unoriented sheet is biaxially stretched in the length direction and the width direction. Here, the stretching in the length direction refers to the uniaxial stretching for imparting molecular orientation in the length direction to the sheet, which is usually implemented by the peripheral speed difference of the longitudinal stretching machine roller. The stretching can be carried out in one stage, or it can be carried out in multiple stages using multiple rollers. The stretching ratio varies depending on the type of resin, and is usually preferably 2 to 10 times. For example, in the case of using a thermoplastic resin, i.e., polyethylene terephthalate or polyethylene naphthalate, which is a thermoplastic resin preferably used to form a crystalline thermoplastic resin layer of the film of the present invention, it is particularly preferred to use 2 to 7 times. In the case where the ratio is excessively increased in the stretching process in the length direction to make it strongly oriented, due to the shrinkage (neck down) in the width direction, in addition to not being able to obtain a sufficient sheet width, sometimes the thickness unevenness in the length direction and / or width direction after the width direction stretching becomes larger. The stretching temperature is preferably set within a range of from the glass transition temperature of the thermoplastic resin layer having the highest glass transition temperature among the thermoplastic resin layers constituting the sheet to the glass transition temperature + 100°C.

[0089] The uniaxially stretched sheet is then stretched in the width direction, but before that, surface treatments such as corona treatment, flame treatment, and plasma treatment are performed as needed, and then an easy-adhesion layer that can impart functions such as easy slip, easy adhesion, and antistatic properties can be imparted by online coating. In the online coating process, the easy-adhesion layer can be coated on a single side of the laminated film, or it can be coated on both sides of the sheet simultaneously or sequentially. Stretching in the width direction refers to stretching used to impart orientation in the width direction to the sheet, and a tenter is usually used to hold the two ends of the sheet in the width direction with clips, and the sheet is transported while the distance between the relative clips is expanded. The stretching ratio varies depending on the type of resin, and is generally preferably 2 to 10 times. For example, when using a thermoplastic resin, namely polyethylene terephthalate or polyethylene naphthalate, which is preferably used to form the crystalline thermoplastic resin layer of the film of the present invention, it is particularly preferred to use 2 to 7 times. The stretching temperature is preferably from the glass transition temperature of the resin having the highest glass transition temperature among the resins constituting the sheet to the glass transition temperature + 120°C.

[0090] The biaxially stretched sheet is heat treated in a tenter at a temperature above the stretching temperature and below the melting point of the thermoplastic resin layer with the highest melting point among the thermoplastic resin layers constituting the sheet, preferably at a temperature above the stretching temperature and below -30°C from the melting point of the thermoplastic resin layer with the highest melting point among the thermoplastic resin layers constituting the sheet. Then, the sheet is cooled uniformly and slowly, cooled to room temperature and wound up. In addition, as needed, in order to impart thermal dimensional stability, a relaxation treatment may be used in the longitudinal direction and / or the width direction between the heat treatment and the slow cooling.

[0091] Here, in order to obtain a sheet satisfying 0.50≤|S(150)-S(100)| suitable for the film of the present invention, it is preferred to enhance the orientation in the length direction by the longitudinal stretching ratio and the longitudinal stretching temperature. For example, when polyethylene terephthalate (PET) is used as one of the thermoplastic resins, the desired sheet can be easily obtained by making the longitudinal stretching temperature below 95°C or / and the longitudinal stretching ratio above 3.5 times. Similarly, it is also preferred to enhance the orientation in the direction (width direction) orthogonal to the length direction by the transverse stretching temperature and the transverse stretching ratio. For example, when PET is used as one of the thermoplastic resins, the desired sheet can be easily obtained by making the transverse stretching temperature below 110°C or / and the transverse stretching ratio above 3.8 times. In addition, in order to suppress the difference in the thermal shrinkage behavior of the sheet in the length direction and the direction orthogonal thereto, it is preferred to adjust the longitudinal stretching conditions and the transverse stretching conditions. Specifically, the heat shrinkage behavior can be easily made isotropic by setting the difference between the longitudinal stretch ratio and the transverse stretch ratio to 0.8 times or less, or setting the difference between the longitudinal stretch temperature and the transverse stretch temperature to 15° C. or more and 50° C. or less.

[0092] In addition, in the manufacturing method of the sheet material suitable for the film of the present invention, it is preferred that the heat treatment temperature after stretching is below the melting point of at least one thermoplastic resin and above the melting point of at least one remaining thermoplastic resin. At this time, the thermoplastic resin on one side maintains a high orientation state, and the orientation of the thermoplastic resin on the other side is relaxed, so in addition to being able to easily set the refractive index difference of these resins, it is also possible to impart a higher thermal shrinkage behavior to the thermoplastic resin that maintains the orientation. In addition, for example, in the case of having two thermoplastic resin layers (A1 layer, B1 layer) with different main components, the A1 layer is composed of a crystalline polyester (crystalline polyester A1), and the B1 layer is composed of a non-crystalline polyester and a crystalline polyester different from the crystalline polyester A1 (crystalline polyester B1), as the heat treatment temperature, it is preferably below the melting point of the crystalline polyester A1 and the crystalline polyester B1. At this time, in addition to the orientation of the crystalline polyester A1, the orientation of the crystalline polyester B1 is also maintained, so a more preferred thermal shrinkage behavior can be imparted.

[0093] In addition, since the relaxation treatment is performed to suppress the heat shrinkage behavior, it is also preferred that the sheet material suitable for the film of the present invention is not subjected to the relaxation treatment, and the preferred degree of relaxation treatment is a relaxation treatment ratio of 0% to 5% relative to the sheet width before the relaxation treatment. Although it varies depending on the type of thermoplastic resin used, for example, in the case of polyethylene terephthalate and amorphous polyester that is completely melted in the heat treatment step, a sheet material with the best heat shrinkage behavior can be obtained when the relaxation treatment ratio is in the range of about 0% to 1% relative to the film width before the relaxation treatment.

[0094] Next, the method for manufacturing the film of the present invention is described. The method for manufacturing the film of the present invention comprises a re-annealing step of subjecting a sheet satisfying 0.50≤|S(150)-S(100)| to heat treatment at a temperature above 110°C and below 140°C. More preferably, there is a re-annealing step in which the sheet satisfies 0.40<|S(120)-S(100)|. The preferred re-annealing step for obtaining the film of the present invention is described below. The so-called re-annealing step is a step of subjecting a sheet that has been wound once to heat treatment again. The sheet satisfying 0.50≤|S(150)-S(100)| obtained by the above method usually does not satisfy 0.00≤|S(120)-S(100)|≤0.40. However, by heat treating the sheet satisfying 0.50≤|S(150)-S(100)| again at a temperature above 110°C and below 140°C, a film satisfying 0.50≤|S(150)-S(100)| and 0.00≤|S(120)-S(100)|≤0.40 can be obtained.

[0095] Generally, when the shrinkage at a certain temperature is to be reduced, reheat treatment at a temperature of -10°C or higher is effective. Therefore, in order to reduce S(120), i.e., the shrinkage at 120°C, annealing at a temperature of 110°C or higher is effective. On the other hand, when annealing is performed at a temperature of 140°C or higher, S(150), i.e., the shrinkage at 150°C, is also reduced, and the resulting film may not satisfy 0.50≤|S(150)-S(100)|. However, even when annealing is performed at a temperature of 140°C or higher, when the annealing time is short (i.e., the sheet conveying speed is fast), 0.50≤|S(150)-S(100)| may be satisfied. Similarly, even when annealing is performed at a temperature below 110°C, when the annealing time is sufficient, 0.00≤|S(120)-S(100)|≤0.40 may be satisfied. However, if the difference between the desired temperature for reducing shrinkage and the reheat treatment temperature is too large, problems may occur in film planarity and shrinkage controllability. Therefore, the preferred heat treatment temperature in the reannealing step is 110°C or higher and lower than 140°C.

[0096] In addition, the present invention has found that even when the above-mentioned sheet satisfies 0.40<|S(120)-S(100)|, by reheating at above 110°C and below 140°C, it is possible to obtain a film in which S(120) is reduced while maintaining a high S(150), that is, a film that satisfies 0.50≤|S(150)-S(100)| and 0.00≤|S(120)-S(100)|≤0.40.

[0097] Furthermore, when the width direction is set to the X direction, the shrinkage rate in the width direction is easily within the above range by making the width direction free in the reannealing process, that is, by making the sheet material unconstrained in the width direction. In addition, when the length direction is the X direction, even if the winding speed in the length direction is reduced by 0.5 to 5% compared to the unwinding speed, the shrinkage rate in the length direction is easily within the above range. Furthermore, even if a staged cooling zone is provided after the heat treatment, the shrinkage rate can be adjusted.

[0098] The film of the present invention is suitable for use as a laminated glass having an intermediate layer and a support after a step of laminating a functional layer accompanied by heating. That is, a laminated structure in which a functional layer is laminated on at least one side of the film of the present invention can be formed. Here, the functional layer refers to a layer having functions not possessed by the film of the present invention, such as an easy-adhesion layer, a hard coating layer, an abrasion-resistant layer, an anti-damage layer, an anti-reflection layer, a color correction layer, an ultraviolet absorbing layer, a heat absorbing layer, a printing layer, a gas barrier layer, an adhesive layer, a conductive layer, a protective layer, etc.

[0099] When a functional layer is stacked on the film of the present invention to form a stacked structure, a coating agent serving as the basis of the functional layer is sometimes applied to the film, and a heating process of 100°C or higher and less than 130°C is required to remove the solvent or solidify it. At this time, when the film does not satisfy 0.00≤|S(120)-S(100)|≤0.40), that is, when |S(120)-S(100)|>0.40, deformations such as wrinkles may sometimes occur during the heating process. In this case, the functional layer may also crack, deform, curl, etc., and may sometimes fail to exhibit the functions of the functional layer. Therefore, as a manufacturing method for obtaining the stacked structure of the present invention, it is preferred to have a process for performing heat treatment at a temperature of 100°C or higher and less than 130°C.

[0100] In the laminated structure of the present invention, at least one layer of the functional layer is preferably a conductive layer. The conductive layer is not particularly limited as long as it can function by energizing, and can be formed by conductive fibers such as silver nanowires and carbon nanotubes, or a combination thereof. In addition, it can also be a film with Ag, Cu, or a metal oxide as a constituent component. They can be used alone or in combination of two or more, and the conductive layer composed of them generally functions as a transparent electrode. As metal oxides, ITO (In2O3: Sn), ATO (SnO2: Sb), FTO (SnO2: F), AZO (ZnO: Al), GZO (ZnO: Ga), etc. can be exemplified. Among them, Ag or Cu also have the possibility of deterioration due to oxidation, so the conductive layer is preferably a metal oxide, and a film with ITO as the main component is particularly preferred, where the main component refers to a component with a content of more than 50% by mass and less than 100% by mass in the conductive film.

[0101] In addition, in the laminated structure of the present invention, it is preferred that the functional layer has a plurality of layers, at least one of which is a second film having an absolute value of a shrinkage rate of 0.20% or less at 120°C. Here, "at least one functional layer having an absolute value of a shrinkage rate of 0.20% or less at 120°C" means that the absolute value of the shrinkage rate at 120°C in any one direction in the plane of the second film and in each direction rotated from the direction to an in-plane direction parallel to the plane at intervals of 5° to 180° is 0.20% or less.

[0102] For example, when a functional layer is stacked on the film of the present invention, in order to prevent damage or contamination to the film due to processing, etc., a protective layer of a protective film is sometimes stacked in advance as a functional layer on the surface opposite to the surface on which the functional layer is stacked. Alternatively, even if a functional layer is not stacked, there are cases where a protective layer is stacked to prevent damage or contamination to the film caused by processing, etc. in the process of re-annealing the film of the present invention. The protective layer is sometimes composed of a film different from the film of the present invention, and the film constituting the protective layer is referred to as the second film of the present invention. By suppressing the absolute value of the shrinkage rate of the second film at 120°C to less than 0.20%, in the heating process of stacking other functional layers on the opposite surface thereof, the generation of curling caused by the difference in shrinkage rate between the second film as a protective layer and the film of the present invention can be suppressed, and the functional layer on the surface on the opposite side of the protective layer can be easily stacked without damaging the function. Therefore, the absolute value of the shrinkage rate of the above-mentioned second film at 120°C is preferably less than 0.20%.

[0103] In addition, it is preferred that when the orientation angle of the film of the present invention is set to θb and the orientation angle of the second film is set to θf, a laminated structure with |θb-θf|≤30° is bonded. The orientation angle mentioned here refers to the direction of the maximum refractive index on the film, which is actually measured by an optical method. In addition, |θb-θf| takes the maximum value in the length direction and the two ends of the length direction of the bonded film. In the sequential biaxial stretching used in the manufacture of general biaxially stretched films, a clamping tenter is used, especially when stretching in the width direction of the film. However, in this method, in the process of stretching along the track while holding the two ends of the film with a clamp, the stresses on the central part of the film and the part near the clamp in the flow direction of the film are different, so the difference in orientation angle can be seen in the width direction of the film. The biaxially stretched film manufactured in this way tends to shrink in the direction of the orientation angle by heating. The orientation angle θb of the film of the present invention and the orientation angle θf of the second film are |θb-θf|≤30°, which means that the difference in orientation angles between the film of the present invention and the second film is small, and the curling caused by the difference in orientation angles between the film of the present invention and the second film serving as the protective layer can be suppressed, and the functional layer can be easily stacked on the surface on the opposite side of the protective layer without damaging the function.

[0104] There is no particular limitation on the method for controlling the orientation angle, but when the orientation angle of a film is to be increased by sequential biaxial stretching in the longitudinal and transverse directions, it is effective to increase the orientation in the film flow direction of a uniaxially stretched film by lowering the longitudinal stretching temperature and / or increasing the longitudinal stretching ratio, and to weaken the orientation in the film width direction during the heat treatment step by lowering the transverse stretching temperature and / or increasing the heat treatment temperature.

[0105] In addition, when it is desired to reduce the orientation angle of the film, it is effective to reduce the orientation of the film flow direction of the uniaxially stretched film by increasing the longitudinal stretching temperature and / or decreasing the longitudinal stretching ratio, and to reduce the orientation of the film width direction by increasing the transverse stretching temperature and / or decreasing the heat treatment temperature. Furthermore, it is also effective to set a difference in the transverse stretching speed and / or stretching temperature in the transverse stretching process. Specifically, it can be cited that when the transverse stretching interval is divided into two parts, the stretching amount of the film at the middle point of the transverse stretching interval (film width at the measurement point - film width before stretching) is more than 60% of the stretching amount at the end of the transverse stretching interval. In addition, it is also effective to change the temperature during transverse stretching in stages. Specifically, when the transverse stretching interval is divided into two parts, it is also effective to set a difference of more than 20°C in the atmospheric temperature of the stretching interval in the first half and the second half compared to the middle point of the transverse stretching interval.

[0106] In addition, from the viewpoint of easily stacking the functional layer on the surface opposite to the protective layer without damaging the function, the laminated structure of the present invention preferably has functional layers on both sides, one of which is a conductive layer and the other is a second film having an absolute value of shrinkage at 120°C of less than 0.20%.

[0107] The laminated structure of the present invention preferably has at least one continuous reflection band with a reflectivity of 30% or more over a wavelength range of 20 nm or more in a reflectivity curve measured from at least one surface, more preferably over a wavelength range of 100 nm or more, and even more preferably over a wavelength range of 300 nm or more.

[0108] The reflectivity of each wavelength can be measured as a relative reflectivity based on a white plate of aluminum oxide, and the details are described later. "On at least one surface" means that the requirements are met when the reflectivity is measured by irradiating at least one surface with light. In addition, as a method for forming a stacked structure having a reflectivity of more than 30% and at least one continuous reflection band over a wavelength range of more than 20nm, a method of adjusting the number of layers of the film of the present invention constituting the stacked structure can be cited. More specifically, the more the number of layers is increased, the wider the range of the reflection band can be.

[0109] The laminated structure of the present invention preferably has the reflection band within the wavelength range of 850nm to 1200nm. By adopting such a method, infrared rays can be reflected and heat insulation is excellent. For example, by sandwiching such a laminated film between two sheets of glass, a laminated glass capable of maintaining high heat insulation performance for a long time can be obtained.

[0110] The laminated structure of the present invention preferably has a visible light transmittance of 70% or more. By adopting such a method, reflection in the visible area can be suppressed, coloration and glare can be reduced, and visual recognition is excellent. For example, by sandwiching such a laminated structure between two sheets of glass, a laminated glass with high transparency can be obtained, and it can also be applied to automobile windshields, etc.

[0111] By making the film of the present invention into the above-mentioned laminated film, such a laminated structure can be easily obtained. For more than half of the layers constituting the laminated film, the sum of the optical thickness of the adjacent layers is preferably 400nm to 700nm. The optical thickness mentioned here refers to the product of the layer thickness in each layer and the refractive index of the resin constituting the layer, and the sum of the optical thickness of the adjacent layers becomes the element that determines the wavelength of interference reflection in the laminated film. Since the interference reflection of the laminated film whose sum of the optical thickness of the adjacent layers is 400nm to 700nm usually occurs in the wavelength range of about 800nm ​​to 1400nm, it is easy to make the reflection band exist in the range of 850nm to 1200nm. In addition, the size of the reflectivity increases with the difference of the average refractive index in the plane of the number of layers or adjacent layers. For more than half of the layers, in the laminated film whose sum of the optical thickness of the adjacent layers is 400nm to 700nm, it is easy to effectively improve the average reflectivity in the band of wavelength 850nm to 1200nm.

[0112] For example, when polyethylene terephthalate with a refractive index of 1.66 and polyethylene terephthalate copolymerized with spiroglycol and cyclohexane dicarboxylic acid with a refractive index of 1.55 are used as resins A and B, by stacking more than about 201 layers, the sum of the optical thicknesses of adjacent layers is 400nm to 700nm, and a reflection band with a maximum reflectivity of more than 70% can exist in the range of wavelengths from 850nm to 1200nm. As the in-plane refractive index difference between resins A and B increases, the maximum value of the reflectivity in the reflection band can be increased. If the in-plane refractive index difference is more than 0.3, sufficient reflectivity can be given even with about 51 layers.

[0113] In addition, when polyethylene terephthalate having a refractive index of 1.66 and polyethylene terephthalate copolymerized with spiroglycol and cyclohexanedicarboxylic acid having a refractive index of 1.55 are used as resins A and B, in order to make the sum of the optical thicknesses of adjacent layers 400 to 700 nm, the required layer thickness range is about 120 to 220 nm. In addition, the higher the reflectivity in the reflection band existing in the wavelength range of 850 nm to 1200 nm, the higher the heat insulation performance of the film.

[0114] Another example of a laminated film having an average reflectance of 70% or more in the wavelength band of 850 to 1200 nm is a laminated film in which the optical thicknesses of the adjacent A layer and B layer satisfy the following Formulas 1 and 2 at the same time.

[0115] Formula 1: λ=2(n α d α +n β d β )

[0116] Formula 2: n α dα =n β d β

[0117] Where λ is the reflection wavelength, n α is the in-plane refractive index of layer A, d α is the thickness of layer A, n β is the in-plane refractive index of layer B, d β Is the thickness of layer B. By having a layer thickness distribution that satisfies both formula 1 and formula 2, even-numbered reflections can be eliminated. Therefore, while increasing the average reflectivity in the wavelength range of 850nm to 1200nm, it is possible to reduce the average reflectivity in the wavelength range of 400 to 700nm as the visible light region, so that a transparent film with high heat-ray cutoff performance can be obtained. Usually, the refractive index of the film after thermoplastic resin molding and stretching is about 1.4 to 1.9, so by making the thickness ratio of the adjacent A layer to the B layer (the thickness of the A layer / the thickness of the B layer) be 0.7 or more and 1.4 or less, a film that suppresses even-numbered reflections can be obtained. Therefore, the thickness ratio of the adjacent A layer to the B layer (the thickness of the A layer / the thickness of the B layer) is preferably 0.7 or more and 1.4 or less. More preferably, it is 0.8 or more and 1.2 or less.

[0118] As one embodiment of the film of the present invention, the refractive index of at least one surface of the laminated film can be 1.68 or more and 1.80 or less. When the refractive index is lower than 1.68, it is sometimes difficult to have a reflection band with a reflectivity of 30% or more over 20 nm in the wavelength range of 300 nm to 2500 nm. When the refractive index is higher than 1.80, the stacking property of resin A and resin B deteriorates due to the large difference in chemical structure, and sometimes the turbidity of the multilayer film or the interface peeling between layer A and layer B becomes significant.

[0119] As an example of a method for making the refractive index of at least one surface of the laminated film be 1.68 or more and 1.80 or less, a method in which the main dicarboxylic acid unit of the resin A is a naphthalene dicarboxylic acid unit can be cited. By adopting such a form, the in-plane refractive index difference between the A layer and the B layer can be set, and a laminated polyester film with better reflective performance can be easily obtained. In addition, in order to increase the in-plane refractive index difference between the A layer and the B layer, the resin B is preferably an amorphous resin. In the resin A of the film of the present invention, in order to make the dicarboxylic acid constituent contain naphthalene dicarboxylic acid, a method in which the dicarboxylic acid constituent of the raw material polyester resin constituting the resin A contains naphthalene dicarboxylic acid can be used.

[0120] The film of the present invention is also suitable as a film used for laminated glass having an intermediate layer and a support body after the process of laminating the functional layer accompanied by heating. Laminated glass formed by laminating the intermediate layer and the support body on at least one side of the film is generally laminated under adhesive pressure, and is preferably press-formed under heating at 120°C to 160°C. When press-forming under heating at 120°C to 160°C, by making the film satisfy 0.50≤|S(150)-S(100)|, it is possible to suppress uneven pressing caused by uneven thickness of the intermediate layer during the production of the laminated glass and uneven deformation of the film caused by the difference in thermal shrinkage stress between the intermediate layer and the film, and obtain laminated glass with good appearance.

[0121] The film of the present invention is suitable for laminated glass. It is particularly preferred that polyvinyl butyral is laminated as an intermediate layer and glass is laminated as a support on both sides of a laminated structure having a functional layer laminated on the film of the present invention. That is, it is preferred to have a laminated glass having glass 1, an intermediate layer 1, the above-mentioned laminated structure, an intermediate layer 2, and glass 2 in this order. The laminated glass of the present invention is formed using the film of the present invention. Here, formed using the film of the present invention means using at least one of the film of the present invention or the laminated structure of the present invention. In addition, the glass used as a support is not particularly limited, and commonly used transparent plate glass and the like can be used. For example, transparent glass, float glass, frosted glass, template glass, mesh glass, wired glass, infrared absorbing plate glass, infrared reflecting plate glass, green glass, etc. can be listed. The glass is preferably transparent, and its thickness is preferably 0.5 mm to 5.0 mm.

[0122] In the laminated glass formed by using the laminated structure of the present invention, the glass 1 is preferably located on the sunlight incident side, and the conductive layer of the laminated structure is located on the side of the intermediate layer 1. By setting the conductive layer on the sunlight incident side, sunlight can be reflected or absorbed by the conductive layer, and laminated glass with high heat insulation can be formed, which is preferred.

[0123] The laminated glass of the present invention is suitable for use in windows of buildings or automobiles, etc. Automobiles containing laminated glass in which polyvinyl butyral as an intermediate layer and glass as a support are laminated on both sides of a laminated structure in which a functional layer is laminated on the film of the present invention are particularly preferred. Furthermore, automobiles containing laminated glass in which a conductive layer is laminated as a functional layer and optical or thermal functions are exhibited by passing electricity through the conductive layer are preferred.

[0124] As the intermediate layer, in addition to the above, vinyl acetate resin system, vinyl chloride vinyl acetate copolymer system, ethylene vinyl acetate copolymer system, polyvinyl alcohol, polyvinyl butyral, polyvinyl acetal, polyvinyl ether, nitrile rubber system, styrene butadiene rubber system, natural rubber system, chloroprene rubber system, polyamide system, epoxy resin system, polyurethane system, acrylic resin system, cellulose system, polyvinyl chloride, polyacrylate, polyisobutylene and other resins can also be listed. In addition, adhesion regulators, plasticizers, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, colorants, crosslinking agents, etc. can also be added to these intermediate layers. By providing an intermediate layer, the adhesion between the support and the film, the design of the laminated glass, durability, weather resistance, impact resistance and other functions can be improved. In addition, the thickness of the intermediate layer is preferably 10μm to 1mm.

[0125] As a component for improving the designability, there is a colorant, and examples thereof include azo pigments, polycyclic pigments, lake pigments, nitro pigments, nitroso pigments, aniline black, basic blue, phthalocyanine pigments, cyanine pigments, azo dyes, anthraquinone dyes, quinophthalone dyes, methine dyes, condensed polycyclic dyes, reactive dyes, cationic dyes, lanthanum hexaboride, indium tin oxide, antimony tin oxide, cesium tungsten oxide, and the like.

[0126] The forming methods of laminated glass include extrusion lamination, hot melt lamination, heat lamination, press lamination, vacuum lamination, autoclave lamination, etc. Extrusion lamination is a method in which a molten film and an intermediate layer are extruded from a die head into a film shape and laminated on a support body, and then formed into a molded product between two rollers. Hot melt lamination refers to a forming method in which a heat-melted intermediate layer is coated on a film or a support body, and the film and the support body are laminated. Heat lamination is a forming method in which a film, an intermediate layer, and a support body are heated by a heating roller while being pressed together for lamination. Press lamination is a forming method in which a film, an intermediate layer, and a support body are heated, and then pressed together and laminated with a press. The so-called vacuum lamination is a forming method in which a film, an intermediate layer, and a support body are heated, and then the inside of the device is made into a vacuum state, and then pressed and laminated. Autoclave lamination is a forming method in which a film, an intermediate layer, and a support body are heated, and then the inside of the device is pressurized with gas or the like for lamination.

[0127] The film and laminated structure of the present invention can also be applied to molded bodies other than laminated glass, which is described in detail below. As a support body that can be used for a molded product formed using the film or laminated structure of the present invention, for example, a support body made of resin, a support body made of metal or ceramic, etc. can be listed. The surface of the support body can be a plane or a curved surface, and can be any shape. As examples of resins, acrylic resins such as polycarbonate, cyclic polyolefin, polyarylate, polyethylene terephthalate, polymethyl methacrylate, ABS, triacetyl cellulose, etc. can be listed. Although it varies depending on the purpose of the molded body, the support body is preferably transparent, and the thickness of the support body is preferably 0.5mm to 5.0mm.

[0128] Example

[0129] The film of the present invention is described below with reference to specific examples. Even when a thermoplastic resin other than the thermoplastic resin specifically exemplified below is used, the film of the present invention can be obtained in the same manner as long as the description of this specification including the following examples is referred to.

[0130] [Methods for measuring physical properties and evaluating effects]

[0131] The evaluation methods of physical property values ​​and the evaluation methods of effects are as follows.

[0132] (1) Shrinkage rate, shrinkage start temperature, and average change rate

[0133] The measurement was performed using a heat, application, and strain measurement device (TMA / SS6000) manufactured by Seiko Instruments under the following conditions. The sample was cut out in any direction in a plane parallel to the film surface and in each direction rotated from this direction to 180° at intervals of 5°. For each data, the shrinkage rate at each temperature was calculated using the following formula 3 in a manner that at least one data was obtained every 1°C to obtain a heat shrinkage curve. Three measurements were performed in each direction, and the direction in which S(150) was the largest was set as the X direction.

[0134] Sample size: 4mm wide, 15mm long

[0135] Heating range: 25~200℃

[0136] Heating speed: 10℃ / min

[0137] Measuring load: 19.8N

[0138] Temperature 23℃, relative humidity 65%, atmosphere

[0139] Formula 3: Shrinkage rate at temperature T°C S(T) = (L(25)-L(T)) / L(25)×100

[0140] L(T): Length of sample at T℃.

[0141] Based on the obtained heat shrinkage curve, the temperature at which the shrinkage rate S(T) first exceeds 0% is taken as the shrinkage start temperature. Based on the obtained shrinkage rate S(T), the average change rate of the shrinkage rate at 120°C to 150°C (average change rate of the shrinkage rate) is calculated using the following formula 4.

[0142] Formula 4: Average change rate of shrinkage rate = |S(150)-S(120)| / (150-120).

[0143] (2) Number of layers

[0144] The number of layers of the laminated film is determined by observing the sample sliced ​​by an ultra-thin slicer with a transmission electron microscope (TEM). Specifically, a transmission electron microscope JEM-1400Plus (manufactured by JEOL Ltd.) is used to observe the cross section of the laminated film under an accelerating voltage of 100 kV, and the cross-sectional image is obtained to determine the number of layers. In addition, in order to make the contrast difference between the layers larger, a staining technique using an electron stain (RuO4, etc.) is used. In addition, depending on the thickness of each layer, when the thickness of the thin film layer is less than 100nm, it is observed at a direct magnification of 40,000 times, when the thickness of the thin film layer is greater than 100nm and less than 500nm, it is observed at a direct magnification of 20,000 times, and when the thickness is greater than 500nm, it is observed at 1,000 to 10,000 times according to the thickness, and the number of layers is determined based on the contrast difference of the obtained image.

[0145] (3) Layer interface (poor contrast)

[0146] The cross-sectional image obtained in the transmission electron microscope observation of (2) is converted into a compressed image file (JPEG) format, and the position-brightness data is obtained through a line graph along the thickness direction of the laminated film using ImagePro-10 (seller: Hakto Co., Ltd.). Afterwards, a spreadsheet software (Microsoft "Excel" (registered trademark) 2016) is used to perform a 5-point moving average process on the curve obtained by depicting the relationship between position and brightness. During the averaging process, the average brightness is averaged for 5 consecutive measurement positions, and the positions are changed one by one, and the same calculation is continuously processed to obtain the position-brightness curve after the average processing. In the obtained position-brightness curve after the average processing, the position surrounded by the inflection point where the slope changes from positive to negative or from negative to positive is judged as a layer. For each layer obtained by this method, the position-brightness data is then obtained relative to the plane direction of the laminated film (the direction perpendicular to the thickness direction). After calculating the average value and standard deviation of the brightness obtained for each layer, if the difference between the average values ​​of brightness of two adjacent layers is larger than any of the standard deviations of the brightness of adjacent thermoplastic resin layers, the two adjacent layers are determined to be different.

[0147] (4) Differential Scanning Calorimetry (DSC)

[0148] (Strain) used a differential scanning calorimeter EXSTAR DSC6220 produced by Hitachi High Tech Nologies Co., Ltd. The measurement and temperature reading were implemented according to JIS-K-7122 (1987). Specifically, about 5 mg of the sample was heated from 25°C to 300°C at a rate of 10°C / min on an aluminum tray, and the intersection of the baseline when heated from room temperature and the tangent at the inflection point of the step transition part was set as the glass transition temperature Tg (°C). After heating, it was quenched with liquid nitrogen, and when the temperature was raised again under the same conditions, the endothermic peak confirmed on the highest temperature side was taken as the melting point (°C). In addition, the integral value calculated based on the baseline within the range of ±20°C of the melting point at this time was taken as the melting enthalpy (J / g).

[0149] (5) Orientation angle

[0150] A phase difference measuring device (KOBRA-21ADH) manufactured by Oji Instruments Co., Ltd. was used. The sample was cut into 3.5 cm × 3.5 cm, with the length direction of the film in the longitudinal direction. The sample was collected from the center and both ends of the length direction and both ends of the direction perpendicular to the length direction, and the orientation angle of 590 nm at an incident angle of 0° was measured. Based on the obtained results, the orientation angle at the length direction position was set as θ0, and the orientation angle with the largest difference from θ0 was set as θb and θf.

[0151] (6) Curl test

[0152] Assuming the heating process when laminating the functional layer after the protective layer is attached, the degree of curling after the heat treatment is evaluated. As the protective layer, an adhesive film with an adhesive layer on a PET film is used, and it is laminated to the film by hand in a way that bubbles do not enter. Then, the film with the protective layer attached is cut into a size of 20 mm in width and 20 mm in length, and heat treated at 120°C for 1 hour. A windless oven is used for the heat treatment. The height of the four corners of the sample after the heat treatment is measured to evaluate the degree of curling. The evaluation criteria are as follows. In addition, the following layers are used as protective layers.

[0153] <Evaluation Criteria>

[0154] A: All four corners are less than 30mm.

[0155] B: One or two of the four corners are 30 mm or less, and the remaining two or three corners are greater than 30 mm and 50 mm or less.

[0156] C:Except A, B and D.

[0157] D: All four corners are greater than 50mm.

[0158] <Protective layer>

[0159] The heat shrinkage curve of the adhesive film was obtained by the method (1). The measurement was performed three times in each direction, and the absolute value of the maximum value of the shrinkage ratio S(120) at 120°C was used as follows.

[0160] Adhesive film 1: an adhesive film having a shrinkage rate of 0.15% at 120°C.

[0161] Adhesive film 2: an adhesive film having a shrinkage rate of 0.28% at 120°C.

[0162] Adhesive film 3: an adhesive film having a shrinkage rate of 0.35% at 120°C.

[0163] <Lamination direction>

[0164] The film and the protective layer were bonded together in the following two directions at the orientation angles measured by the method (5).

[0165] Parallel direction: The direction in which the orientation angle θb of the film and the orientation angle θf of the protective layer coincide with each other. In this case, θb-θf is the difference between the absolute values ​​of θb and θf measured in (5).

[0166] Cross direction: The direction in which the orientation angle θb of the film and the orientation angle θf of the protective layer are perpendicular to each other. In this case, θb-θf is the sum of the absolute values ​​of θb and θf measured in (5).

[0167] (7) Production of laminated glass

[0168] Laminator 0303S manufactured by Nisshinbo Co., Ltd. was used, and the glass 1, the intermediate layer 1, the film and laminated structure of the embodiment or comparative example, the intermediate layer 2, and the glass 2 were stacked in this order, and pressed for 30 minutes at a temperature of 140°C and 1.5 MPa. Transparent plate glass with a width of 100 mm × a length of 100 mm × a thickness of 2 mm was used as the glass 1 and the glass 2, and a PVB film with a thickness of 0.4 mm was used as the intermediate layer 1 and the intermediate layer 2. In addition, when the functional layer is a protective layer, the protective layer is peeled off and the laminated glass is made with the film, and when the functional layer is a conductive layer, the laminated glass is made with a laminated structure with a conductive layer laminated.

[0169] (8) Laminated glass appearance (concave and convex)

[0170] The molded article placed under a fluorescent lamp was visually evaluated at an angle of 20°, 50°, and 70° relative to the normal direction of the evaluation part. The evaluation criteria are as follows.

[0171] A: No bumps or depressions can be seen.

[0172] B: The bumps and depressions appear minimal.

[0173] C: Concavoconvexities can be seen.

[0174] (9) Preparation of glass laminate

[0175] LAMINATOR 0303S manufactured by Nisshinbo Co., Ltd. was used, and transparent plate glass, an intermediate layer, and the film of Example 30 were stacked in this order, and pressed for 30 minutes at a temperature of 140° C. and 1.5 MPa, thereby producing a glass laminate. The transparent plate glass used was a transparent plate glass of 100 mm in width×100 mm in length×2 mm in thickness. A PVB film was used as the intermediate layer, and a film of 0.4 mm in thickness was used.

[0176] (10) Lamination of Conductive Layer 1

[0177] As the conductive layer 1, an ITO film (indium / tin = 95 / 5 molar ratio, thickness 0.2 μm, vacuum degree 1×10 -3 Pa, the vacuum degree during gas introduction was 0.10 Pa, and the gas ratio Ar / O2=99 / 1).

[0178] (11) Lamination of Conductive Layer 2

[0179] As the conductive layer 2 , a coating liquid containing silver nanowires was applied using a spin coater at room temperature at 500 rpm and then dried at 70° C. for 10 minutes to form a transparent conductive film containing silver nanowires.

[0180] (12) Deformation test of conductive layer

[0181] After the conductive layer 1 was laminated by the method described in (10) and the conductive layer 2 was laminated by the method described in (11), a heat treatment was performed at the temperature described in Table 2-2 and Table 3-2 for 1 hour in a windless oven, and the deformation of the conductive layer was evaluated by visual inspection. The evaluation criteria are as follows.

[0182] A: There is no change in appearance before and after heating treatment.

[0183] B: After the heat treatment, a change in appearance such as whitening was slightly observed in a part of the sample.

[0184] C: After the heat treatment, a change in appearance such as whitening was slightly observed throughout the sample.

[0185] D: After the heat treatment, changes in appearance such as whitening were significantly observed in the entire sample.

[0186] (13) Evaluation of lamination and deformation of hard coating

[0187] A coating material containing 60 parts by weight of an isocyanate compound composed of an isocyanurate of hexamethylene diisocyanate with respect to 100 parts by weight of a polyester compound and adjusted to a solid content concentration of 40% was prepared, and a slurry of cesium tungsten oxide particles Cs0.33WO3 with a solid content concentration of 18.5% was further added to the coating material at a weight ratio of 3:5 as a coating material for forming a heat radiation absorption layer. The coating material was coated on one side with a wire bar coater, dried at 110°C for 10 minutes, and irradiated with 500 mJ / cm by a UV irradiation device. 2 The coating film was cured by ultraviolet light to form a hard coating layer. The deformation of the hard coating layer in the drying process when the hard coating layer was formed was visually evaluated. The evaluation criteria are as follows.

[0188] A: Curling of the film and change in the appearance of the hard coat layer were not observed.

[0189] B: Curling of the film and changes in the appearance of the hard coat layer were observed.

[0190] (14) Reflectivity

[0191] The reflectivity of a sample cut out of 5 cm × 5 cm was measured using the basic structure of an integrating sphere attached to a spectrophotometer (U-4100 Spectrophotomater) manufactured by Hitachi. In this measurement, the measurement was performed using the auxiliary white plate of aluminum oxide attached to the device as a reference. In the reflectivity measurement, the length direction of the sample was set as the vertical direction and placed behind the integrating sphere. The reflectivity was measured under the following conditions, and the average reflectivity in the wavelength band of 850 nm to 1200 nm was calculated.

[0192] <Measurement conditions>

[0193] Slit: 2nm (visible) / automatic control (infrared)

[0194] Gain: 2

[0195] Scanning speed: 600nm / min

[0196] Starting wavelength: 2600nm

[0197] End wavelength: 240nm

[0198] Sampling interval: 1nm

[0199] Angle of incidence: 10°

[0200] <Incident surface>

[0201] When the functional layer is a protective layer: Film surface

[0202] When the functional layer is a conductive layer (conductive layer 1 and conductive layer 2): conductive layer

[0203] When one functional layer is a conductive layer and the other functional layer is a protective layer:

[0204] When the functional layer is a hard coating: hard coating surface.

[0205] (15) Transmittance

[0206] The average transmittance in the wavelength band of 400 nm to 700 nm was determined as the visible light transmittance by measuring under the following conditions using a standard configuration (solid measurement system) of a spectrophotometer (U-4100 Spectrophotomater) manufactured by Hitachi, Ltd.

[0207] <Measurement conditions>

[0208] Slit: 2nm (visible) / automatic control (infrared)

[0209] Gain: 2

[0210] Scanning speed: 600nm / min

[0211] Starting wavelength: 700nm

[0212] End wavelength: 400nm

[0213] Sampling interval: 1nm

[0214] Angle of incidence: 0°.

[0215] (16) Thermal insulation

[0216] The total energy transmittance (Tts) transmitted through the laminated glass produced by (7) and the glass laminate produced by (9) was measured in accordance with ISO13837:2008 "Road vehicles - Safety-classified materials - Method for determination of solar transmittance", with glass 1 as the incident surface in the case of laminated glass and with transparent plate glass as the incident surface in the case of glass laminate. The total energy transmittance (Tts) transmitted through the laminated glass was evaluated in the following four stages.

[0217] A: The total energy transmittance (Tts) through the laminated glass is 50% or less.

[0218] B: The total energy transmittance (Tts) through the laminated glass is greater than 50% and less than 70%.

[0219] C: The total energy transmittance (Tts) through the laminated glass is 70% or more and less than 80%.

[0220] D: The total energy transmittance (Tts) through the laminated glass is 80% or more.

[0221] (17) Film quality

[0222] As the quality of the film, the presence or absence of scratches on the film was visually evaluated.

[0223] A: There are almost no visible scratches on the film.

[0224] B: There are some scratches on the film.

[0225] (18) Refractive index of layer A of the laminated film

[0226] The refractive index of the outermost layer of the film was measured using a prism coupler SPA-400 manufactured by Silon Tech Nologia Co., Ltd. The wavelength of the laser used in the measurement was 633 nm, and the in-plane refractive index was measured for the two outermost layers in the X direction and in the direction (Y direction) rotated 90° from the X direction parallel to the film surface, and the average of these values ​​was calculated.

[0227] (19) Refractive index of layer B and layer C of the laminated film

[0228] Since the B layer and the C layer are layers inside the laminated film, the refractive index was measured not on the film itself but on a single-layer film of the B layer and the C layer produced under the same stretching conditions and heat treatment conditions as the film, using a prism coupler SPA-400 manufactured by Silon Tech Nologia Co., Ltd. The wavelength of the laser used in the measurement was 633 nm, and the in-plane refractive index was measured in the X direction and in each direction (Y direction) rotated 90° from the X direction parallel to the film surface, and the average of these values ​​was calculated.

[0229] (Resin for film)

[0230] The resin used in the embodiments of the present invention is described below. In addition, the refractive index represents the in-plane refractive index (the average value of the refractive index in the X direction and the Y direction) after stretching the sheet composed of each resin under the stretching conditions described in the embodiments. In addition, within the range of the stretching conditions described in the embodiments, the in-plane refractive indexes all represent the same value.

[0231] Resin 1: a homopolymer of polyethylene terephthalate resin (IV = 0.65, in-plane refractive index = 1.66) showing crystallinity with a glass transition temperature of 78°C, a melting point of 254°C, and a melting enthalpy of 40 J / g

[0232] Resin 2: A non-crystalline polyethylene terephthalate copolymer resin (IV = 0.72, in-plane refractive index = 1.54) having a glass transition temperature of 78°C and copolymerized with 20 mol% of a cyclohexanedicarboxylic acid component relative to the total acid component and 20 mol% of a spiroglycol component relative to the total diol component.

[0233] Resin 3: A crystalline polyethylene terephthalate resin (IV = 0.65, in-plane refractive index = 1.62) obtained by copolymerizing isophthalic acid at 10 mol% and showing a glass transition temperature of 79°C, a melting point of 230°C, and a melting enthalpy of 12 J / g.

[0234] Resin 4: A non-crystalline polyethylene terephthalate resin (IV = 0.73, in-plane refractive index = 1.57) containing 33 mol % of copolymerized cyclohexanedimethanol and having a glass transition temperature of 80°C.

[0235] Resin 5: Amorphous homopolymeric methyl methacrylate resin (in-plane refractive index = 1.49) having a glass transition temperature of 101°C.

[0236] (Example 1)

[0237] When two thermoplastic resin layers with different main components are respectively set as A1 layer and B1 layer, resin 1 is used as the thermoplastic resin constituting the A1 layer, and resin 2 is used as the thermoplastic resin constituting the B1 layer. Resin 1 and resin 2 are melted at 280°C in different extruders, and foreign matter and the like are removed by passing through 5 FSS-type leaf disk filters. Then, a gear pump is used to meter while extruding so that the discharge ratio (stack ratio) becomes resin 1 / resin 2=1 / 1.07, and the flows are merged in a 501-layer feed block. In addition, the two surface layers are made of resin 1, and the A1 layer composed of the adjacent resin 1 and the B1 layer composed of the resin 2 satisfy the above formulas 1 and 2 from one surface of the film to the opposite side, so that the thickness of the final A1 layer is changed in the range of 130nm to 180nm, and the thickness of the final B1 layer is changed in the range of 137nm to 190nm in a geometric progression (but the thickness of the A1 layer located in the two surface layers is finally adjusted to 10μm). Next, the obtained molten laminate was supplied to a T-die and formed into a sheet, and then rapidly cooled and solidified on a casting roll maintained at a surface temperature of 25°C while applying an electrostatic voltage of 8 kV with a metal wire to obtain an unoriented sheet. The unoriented sheet was longitudinally stretched by the roller circumferential speed difference at a temperature of 90°C and a stretching ratio of 3.3 times to obtain a uniaxially oriented sheet. Then, the two ends of the obtained uniaxially oriented sheet were clamped with clips and guided to a tenter, and after being transversely stretched at a temperature of 100°C and a stretching ratio of 4.0 times, a heat treatment of 10 seconds at 205°C and a relaxation treatment of 3% in the width direction was performed, and then cooled at 150°C for 10 seconds to obtain a sheet with a thickness of 80 μm. The sheet thus obtained was re-annealed in a hot air oven at 130°C, under the conditions of freedom in the width direction (the sheet is not constrained in the sheet width direction) and a winding tension of 60N in the longitudinal direction, so that the oven passage time was 60 seconds to obtain a film. The evaluation results of the obtained sheets and films are shown in Table 1-1 and Table 1-2. In the curling test, the sheets and films were bonded in a parallel direction.

[0238] (Examples 2 to 5, 8, 10 to 11, 14 to 17)

[0239] Sheets and films were obtained and evaluated in the same manner as in Example 1 except that the heat treatment temperature, the presence or absence of reannealing treatment and its temperature were as shown in Table 1-1, and the protective layer in the curling test was as shown in Table 1-2. The evaluation results are shown in Table 1-2.

[0240] (Example 6)

[0241] Sheets and films were obtained and evaluated in the same manner as in Example 1, except that the thermoplastic resin layer fed into each extruder was only resin 1. The evaluation results are shown in Tables 1-1 and 1-2.

[0242] (Example 7)

[0243] When three thermoplastic resin layers with different main components are set as A2 layer, B2 layer, and C2 layer, respectively, resin 1 is used as the thermoplastic resin constituting the A2 layer, resin 3 is used as the thermoplastic resin constituting the B2 layer, and resin 4 is used as the thermoplastic resin constituting the C2 layer. Resin 1, resin 3, and resin 4 are melted at 270°C, 270°C, and 280°C respectively by different extruders, and after passing through 7 FSS-type leaf disk filters respectively, they are extruded while metering with a gear pump so that the discharge ratio (stacking ratio) is 0.98 for resin 1 / resin 3 and 1.02 for resin 4 / resin 3, and merged in a 601-layer feed block. In addition, at this time, the two surface layers are made of resin 1, and are stacked in a regular arrangement of A2 layer / B2 layer / C2 layer / B2 layer in the thickness direction. Here, the slit length and width in the feed block are designed so that the layer thickness increases monotonically from the outermost surface of one side to the outermost surface of the opposite side except for the two outermost layers. Next, the obtained molten laminate is supplied to a T-die and formed into a sheet, and then, while applying an electrostatic voltage of 8 kV with a metal wire, it is quenched and solidified on a casting roller whose surface temperature is maintained at 25°C to obtain an unoriented sheet. The unoriented sheet is longitudinally stretched at a temperature of 80°C and a stretching ratio of 3.3 times to obtain a uniaxially oriented sheet. Then, the obtained uniaxially oriented sheet is clamped at both ends with clips and introduced into a tenter, and after being transversely stretched at a temperature of 90°C and a stretching ratio of 3.6 times, it is heat treated at 205°C for 10 seconds and relaxed in the width direction by 5%, and cooled at 150°C for 10 seconds to obtain a sheet with a thickness of 80 μm. The obtained sheet is reannealed under the same conditions as in Example 1 to obtain a film. The same adhesive film is also used for the curling test. The evaluation results of the obtained sheets and films are shown in Tables 1-1 and 1-2.

[0244] (Example 9)

[0245] Sheets and films were obtained and evaluated in the same manner as in Example 1 except that resin 5 was used as the thermoplastic resin constituting layer B1, the melting temperature was set to 260°C, the stretching temperature of the unoriented sheet was set to 105°C, and the stretching temperature of the uniaxially oriented sheet was set to 110°C. The evaluation results are shown in Tables 1-1 and 1-2.

[0246] (Example 18)

[0247] Sheets and films were obtained and evaluated in the same manner as in Example 1 except that the extruded resins were combined in a 51-layer feed block. The evaluation results are shown in Tables 1-1 and 1-2.

[0248] (Example 19)

[0249] Sheets and films were obtained and evaluated in the same manner as in Example 1 except that the stretching ratio in the transverse stretching was 3.2 times. The evaluation results are shown in Tables 1-1 and 1-2.

[0250] (Example 20)

[0251] In the curl test, a sheet and a film were obtained in the same manner as in Example 1 except that the sheets were bonded in the cross direction, and the evaluation was performed. The evaluation results are shown in Tables 1-1 and 1-2.

[0252] (Comparative Example 1)

[0253] The sheet obtained by the same method as in Example 1 was made into a film without re-annealing. The evaluation results of the obtained film are shown in Table 1-1 and Table 1-2.

[0254] (Comparative Example 2)

[0255] The sheet obtained by the same method as in Example 2 was made into a film without re-annealing. The evaluation results of the obtained film are shown in Table 1-1 and Table 1-2.

[0256] (Comparative Example 3)

[0257] A sheet was obtained in the same manner as in Example 1 except that the heat treatment temperature was 225° C., and a film was prepared without re-annealing. The evaluation results of the obtained film are shown in Tables 1-1 and 1-2.

[0258] (Comparative Example 4)

[0259] A sheet was obtained in the same manner as in Example 1 except that the heat treatment temperature was 235° C., and a film was prepared without re-annealing. The evaluation results of the obtained film are shown in Tables 1-1 and 1-2.

[0260] (Comparative Example 5)

[0261] The sheet obtained by the same method as in Example 6 was made into a film without re-annealing. The evaluation results of the obtained sheet and film are shown in Table 1-1 and Table 1-2.

[0262] (Comparative Example 6)

[0263] The sheet obtained by the same method as in Example 7 was made into a film without re-annealing. The evaluation results of the obtained sheet and film are shown in Table 1-1 and Table 1-2.

[0264] (Comparative Example 7)

[0265] A film was obtained in the same manner as in Example 3 except that the temperature of the hot air oven in the reannealing treatment was 100° C. The evaluation results of the obtained sheet and film are shown in Table 1-1 and Table 1-2.

[0266] (Comparative Example 8)

[0267] A film was obtained in the same manner as in Example 2 except that the temperature of the hot air oven for the reannealing treatment was 150° C. The evaluation results of the obtained sheet and film are shown in Table 1-1 and Table 1-2.

[0268] (Example 12)

[0269] Sheets and films were obtained in the same manner as in Example 1, and then the conductive layer 1 was laminated by the method described in (8). The evaluation results of the obtained sheets, films and conductive layer laminates are shown in Table 2-1 and Table 2-2. When laminated glass was produced, the conductive layer 1 side was set as the glass 1 side.

[0270] (Example 13)

[0271] Sheets and films were obtained in the same manner as in Example 2, and then the conductive layer 1 was laminated by the method described in (8). The evaluation results of the obtained sheets, films and conductive layer laminates are shown in Table 2-1 and Table 2-2. When laminated glass was produced, the conductive layer 1 side was set as the glass 1 side.

[0272] (Example 21)

[0273] Sheets and films were obtained and evaluated in the same manner as in Example 12 except that the temperature of the deformation test of the conductive layer 1 in (12) was set as shown in Table 2-2. The evaluation results are shown in Tables 2-1 and 2-2.

[0274] (Example 22)

[0275] When producing laminated glass, a sheet and a film were obtained in the same manner as in Example 12 except that the conductive layer 1 side was placed on the glass 2 side, and were evaluated. The evaluation results are shown in Tables 2-1 and 2-2.

[0276] (Example 23)

[0277] Sheets and films were obtained and evaluated in the same manner as in Example 12 except that the functional layer was the conductive layer 2. The evaluation results are shown in Tables 2-1 and 2-2.

[0278] (Example 24)

[0279] When producing laminated glass, a sheet and a film were obtained in the same manner as in Example 23 except that the conductive layer 2 surface was set on the glass 2 side, and were evaluated. The evaluation results are shown in Table 2-1 and Table 2-2.

[0280] (Comparative Example 9)

[0281] A conductive layer was laminated on the film of Comparative Example 2 by the method described in (7). The evaluation results of the obtained film and conductive layer laminate are shown in Table 2-1 and Table 2-2.

[0282] (Comparative Example 10)

[0283] A conductive layer was laminated on the film of Comparative Example 4 by the method described in (7). The evaluation results of the obtained film and conductive layer laminate are shown in Table 2-1 and Table 2-2.

[0284] (Example 25)

[0285] Sheets and films were obtained and evaluated in the same manner as in Example 23 except that one functional layer was set as the conductive layer 2 and the other functional layer was set as the protective layer described in Table 3-2. The evaluation results are shown in Table 3-1 and Table 3-2. In the curling test, the sheets were bonded in a parallel direction.

[0286] (Example 26)

[0287] Sheets and films were obtained in the same manner as in Example 25 except that the protective layer was the protective layer 2 described in Table 3-2, and were evaluated. The evaluation results are shown in Tables 3-1 and 3-2.

[0288] (Example 27)

[0289] Sheets and films were obtained and evaluated in the same manner as in Example 25 except that the sheets were bonded in the cross direction during the curl test. The evaluation results are shown in Tables 3-1 and 3-2.

[0290] (Example 28)

[0291] Sheets and films were obtained and evaluated in the same manner as in Example 26 except that the sheets were bonded in the cross direction during the curl test. The evaluation results are shown in Tables 3-1 and 3-2.

[0292] (Example 29)

[0293] Sheets and films were obtained and evaluated in the same manner as in Example 23 except that the temperature of the deformation test of the conductive layer 2 in (12) was set as shown in Table 3-2. The evaluation results are shown in Tables 3-1 and 3-2.

[0294] (Example 30)

[0295] Sheets and films were obtained in the same manner as in Example 1 except that the functional layer was a hard coat layer, and were evaluated. The evaluation results are shown in Tables 4-1 and 4-2.

[0296]

[0297] In the table, the A1 layer and the A2 layer are described as the A layer, the B1 layer and the B2 layer are described as the B layer, and the C2 layer is described as the C layer.

[0298] The same is true in the following tables.

[0299]

[0300]

[0301]

[0302]

[0303]

[0304] Industrial Availability

[0305] According to the present invention, a film having excellent processing adaptability before and after processing into laminated glass etc. can be obtained. By using the film of the present invention, laminated glass having excellent appearance and design can be obtained, and the laminated glass can be well used for windows etc. of automobiles or buildings etc.

Claims

1. A film having at least one thermoplastic resin layer, When the shrinkage rate at temperature T°C in the heat shrinkage curve is defined as S(T)%, and the direction in which S(150) is the largest in any direction in a plane parallel to the film plane and in each direction rotated from the direction in the plane parallel to the film plane at intervals of 5° to 180° is defined as the X direction, the following conditions are satisfied in the X direction: 0.50≤|S(150)-S(100)|, and 0.00≤|S(120)-S(100)|≤0.

40. 2 . The film according to claim 1 , wherein a shrinkage start temperature in a heat shrinkage curve in the X direction is 110° C. or higher and 170° C. or lower.

3. The film according to claim 1, wherein in the X direction, the shrinkage rate from 100°C to 120°C in the heat shrinkage curve is -0.40% or more and 0.50% or less on average, and the absolute value of the average change rate of the shrinkage rate from 120°C to 150°C is 0.04% / °C or more. 4 . The film according to claim 1 , having a structure in which 51 or more thermoplastic resin layers are stacked. 5 . The film according to claim 1 , comprising the A1 layer and the B1 layer when two thermoplastic resin layers having different main components are respectively provided as the A1 layer and the B1 layer.

6. The film according to claim 1, wherein when three thermoplastic resin layers having different main components are respectively provided as A2 layer, B2 layer and C2 layer, the film has a regular arrangement formed by the A2 layer, the B2 layer and the C2 layer.

7. The film according to claim 1, wherein at least one of the thermoplastic resin layers is a polyester resin layer.

8. A method for producing a thin film, which is the method for producing a thin film according to claim 1, comprising a re-annealing step of heat-treating a sheet satisfying 0.50≤|S(150)-S(100)| at a temperature of 110°C to less than 140°C. 9 . The method for producing a thin film according to claim 8 , wherein the sheet satisfies 0.40<|S(120)−S(100)|. 10 . A laminate structure comprising a functional layer laminated on at least one surface of the thin film according to claim 1 . The laminated structure according to claim 10 , wherein the functional layer is a conductive layer.

12. The laminated structure according to claim 10, wherein the functional layer has a plurality of layers, at least one of which is a second film having an absolute value of a shrinkage rate at 120°C of 0.20% or less. 13 . The laminated structure according to claim 12 , wherein when the orientation angle of the film is θb and the orientation angle of the second film is θf, the laminated structure is bonded so that |θb-θf|≤30°.

14. The laminated structure according to claim 10, comprising the functional layers on both surfaces, wherein one of the functional layers is a conductive layer and the other functional layer is a second film having an absolute value of a shrinkage rate of 0.20% or less at 120°C. 15 . The laminated structure according to claim 10 , which has at least one reflection band having a reflectivity of 30% or more and continuous over a wavelength range of 20 nm or more in a reflectivity curve measured from at least one surface. 16 . The laminated structure according to claim 15 , wherein the reflection band exists within a wavelength range of 850 nm to 1200 nm.

17. The laminated structure according to claim 10, wherein the visible light transmittance is 70% or more.

18. A method for producing a laminated structure, the method for producing a laminated structure according to claim 11, comprising the step of performing a heat treatment at a temperature of 100°C or higher and lower than 130°C when forming the conductive layer. 19 . A laminated glass comprising glass 1 , an intermediate layer 1 , the laminated structure according to claim 11 , an intermediate layer 2 , and glass 2 in this order. 20 . The laminated glass according to claim 19 , wherein the glass 1 is located on the sunlight incident side, and the conductive layer of the laminated structure is located on the intermediate layer 1 side.

21. An automobile comprising the laminated glass according to claim 19, wherein an optical function or a thermal function is exhibited by energizing a conductive layer of the laminated glass.

Citation Information

Patent Citations

  • Laminated film and automotive window glass using the same

    JP2012030563A

  • Multi-layer laminated film

    WO2013137288A1